Design and analysis of non-axisymmetric installed aero-engine exhaust systems - Otter, John J.; Goulos, Ioannis; Christie, Robert; MacManus, David G. (Elsevier, 2020)
In order to increase propulsive efficiency, and hence reduce fuel consumption, future aero-engines are expected to operate with higher bypass ratios and larger fan diameters relative to current in-service engines. As such, propulsion systems are likely to be more closely-coupled with the airframe which is expected to accentuate detrimental aerodynamic interference effects between the engine and airframe. It is therefore crucial that the design of future aero-engine exhaust systems is considered as part of an engine-airframe configuration in order to ensure that the expected benefits of high BPR engines are realised. This work presents the aerodynamic performance and evaluation of a set of novel exhaust systems within complete engine-airframe configurations. The introduction of non-axisymmetric exhaust systems was shown to mitigate the aerodynamic penalties associated with closely-coupled propulsion systems at cruise conditions. Relative to an axisymmetric baseline configuration, the introduction of non-axisymmetric bypass and core nozzles were found to increase the net vehicle force of the engine-airframe configuration by 0.8% and 0.6% respectively. As a result of this work, it can be concluded that non-axisymmetric exhaust systems represent a viable method for reducing aircraft cruise fuel burn.
Keywords: Engine-airframe Integration; Non-axisymmetric; Aero-engine; Computational Fluid Dynamics; Exhaust Nozzle; Class Shape Transformation; Propulsion System Integration